2019
DOI: 10.1021/acsami.8b16786
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Driven Deselenization: A Strategy for Selective Conversion of Copper Ion to Nanozyme and Its Implication for Copper-Related Disorders

Abstract: Synthetic organic molecules, which can selectively convert excess intracellular copper (Cu) ions to nanozymes with an ability to protect cells from oxidative stress, are highly significant in developing therapeutic agents against Cu-related disorder like Wilson’s disease. Here, we report 1,3-bis­(2-hydroxyethyl)-1H-benzoimidazole-2-selenone (1), which shows a remarkable ability to remove Cu ion from glutathione, a major cytosolic Cu-binding ligand, and thereafter converts it into copper selenide (CuSe) nanozym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 72 publications
(97 reference statements)
0
11
0
1
Order By: Relevance
“…The satellite peak at 943.5 eV corresponds to the main peak at 934.6 eV, which belongs to Cu­(II) 2p 3/2 . Meanwhile, the satellite peak at 962.6 eV matches the main peak at 954.6 eV, which is ascribed to Cu­(II) 2p 1/2 . The peak area ratio of Cu­(I) to Cu­(II) was calculated to be 3.56, and thus the as-prepared copper selenide nanoparticles could be expressed as Cu­(I) 1.28 Cu­(II) 0.36 Se.…”
Section: Results and Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The satellite peak at 943.5 eV corresponds to the main peak at 934.6 eV, which belongs to Cu­(II) 2p 3/2 . Meanwhile, the satellite peak at 962.6 eV matches the main peak at 954.6 eV, which is ascribed to Cu­(II) 2p 1/2 . The peak area ratio of Cu­(I) to Cu­(II) was calculated to be 3.56, and thus the as-prepared copper selenide nanoparticles could be expressed as Cu­(I) 1.28 Cu­(II) 0.36 Se.…”
Section: Results and Discussionmentioning
confidence: 86%
“…Meanwhile, the satellite peak at 962.6 eV matches the main peak at 954.6 eV, which is ascribed to Cu(II) 2p 1/2 . 32 The peak area ratio of Cu(I) to Cu(II) was calculated to be 3.56, and thus the asprepared copper selenide nanoparticles could be expressed as Cu(I) 1.28 Cu(II) 0.36 Se. Figure 1f illustrates the high-resolution Se 3d XPS spectrum of Cu(I) 1.28 Cu(II) 0.36 Se nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…The impact of intracellular GSH, particularly in tumor cells in which the cytosolic GSH reaches a high level (1–10 mM), , has the top priority to be investigated because the GSH–copper interaction (Figure a) would potentially lead to dissociation of copper–MTIC coordination and liberation of MTIC into the cytosol (Figure b). GSH interacts with Cu 2+ in the way of both redox reactions and coordination, and multiple forms of GSH-derived products were reported such as Cu­(I)–GSH, Cu­(I)–(GSH) 2 , and Cu­(II)–GSSG complexes under different solvent conditions. The reduction of Cu­(II) to Cu­(I) by a millimole concentration of GSH is likely, which could dissociate MTIC from copper binding and induce a release of MTIC. Chelation between Cu 2+ and GSH to form a GSH–Cu­(II) complex is another factor (Figure a) …”
Section: Resultsmentioning
confidence: 99%
“…Cu is an indispensable micronutrient required by different living forms . However, Cu 2+ ions have been reported to cause serious health disorders if present in concentration beyond the permissible limits. Hence, it has become imperative to develop sensing materials for easy detection of Cu 2+ ions from the contaminated water. Exploration of NC for developing new sensors with improved selectivity and sensitivity to Cu 2+ ions has been reported for efficient analytical applications. Weishaupt et al reported a protein-NC paper sensor for Cu 2+ sensing at the nano- to micromolar level .…”
Section: Introductionmentioning
confidence: 99%